2017
DOI: 10.1161/jaha.117.005835
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Non–Vitamin K Antagonist Oral Anticoagulants Versus Warfarin in Patients With Atrial Fibrillation and Valvular Heart Disease: A Systematic Review and Meta‐Analysis

Abstract: BackgroundThe original non–vitamin K antagonist oral anticoagulant (NOAC) trials in nonvalvular atrial fibrillation (AF) enrolled patients with native valve pathologies. The object of this study was to quantify the benefit–risk profiles of NOACs versus warfarin in AF patients with native valvular heart disease (VHD).Methods and ResultsTrials were identified by exhaustive literature search. Trial data were combined using inverse variance weighting to produce a meta‐analytic summary hazard ratio (HR) and 95% con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
83
1
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(102 citation statements)
references
References 24 publications
9
83
1
9
Order By: Relevance
“…However, such miscoding and misclassification are highly unlikely to be different between patients with normal liver function and those with ILF. The favorable efficacy and safety profiles of NOACs versus warfarin in patients with normal liver function were comparable to the results of meta‐analyses and real‐world data 32, 33, 34. Second, we did not analyze the quality of anticoagulation control as reflected by time in therapeutic range in the warfarin group, given the close relationship between the time in therapeutic range and thromboembolism or bleeding.…”
Section: Discussionmentioning
confidence: 77%
“…However, such miscoding and misclassification are highly unlikely to be different between patients with normal liver function and those with ILF. The favorable efficacy and safety profiles of NOACs versus warfarin in patients with normal liver function were comparable to the results of meta‐analyses and real‐world data 32, 33, 34. Second, we did not analyze the quality of anticoagulation control as reflected by time in therapeutic range in the warfarin group, given the close relationship between the time in therapeutic range and thromboembolism or bleeding.…”
Section: Discussionmentioning
confidence: 77%
“…Data from 2 meta-analyses pooling the results from the sub-analyses of the 4 major trials demonstrated that NOACs can reduce the risk of ischemic stroke in patients with AF and VHD compared with those with AF without VHD [39,40]. Based on these results, patients with AF and specific types of VHD are suitable for anticoagulation with NOACs.…”
Section: Patients With Valvular Heart Diseasementioning
confidence: 99%
“…Они предотвращают развитие сосу-дистых тромбозов, которые являются веду-щей причиной «кардиоваскулярных катаст-роф» (инфаркта миокарда, ишемического ин-сульта, внезапной коронарной смерти), кото-рые наиболее часто становятся причиной ги-бели людей в развитых странах мира. Эти препараты неза-менимы в кардиологии, для профилактики осложнений сахарного диабета, при периферических заболеваниях со-судов (в частности, при тромбофлебите), в хирургической практике для профилактики послеоперационной тромбо-эмболии [1][2][3].…”
unclassified
“…Эти препа-раты эффективнее, чем низкие дозы аспирина (НДА), и значительно удобнее в использовании, чем антагонисты витамина К (АВК), такие как варфарин, ведь действие вар-фарина наступает не сразу (через 5-7 дней), его эффект может существенно различаться у разных пациентов из-за генетического полиморфизма (в частности, по VKORC1 и CYP2C9), при его использовании нужно обязательно контролировать лабораторные показатели свертывания крови -протромбиновый индекс и международное норма-лизованное отношение (МНО), проводить «титрацию» до-зы. Для НОАК такой необходимости нет, поэтому они бы-стро завоевали популярность у врачей и с каждым годом все шире используются в реальной клинической практике [1][2][3].…”
unclassified